GAMBARAN KOMPLIKASI DIABETES MELITUS PADA PENDERITA DIABETES MELITUS - Rif’at, Ivan Dzaki; Hasneli N, Yesi; Indriati, Ganis (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Length of time suffering from diabetes mellitus is closely related to complications and this study aims to see an overview of complications diabetes mellitus in people with diabetes mellitus. Methods: This study used a correlative descriptive design with a cross sectional approach. A sample of 143 respondents used a purposive sampling technique. Using a DM complication questionnaire that has been tested for validity and reliability. Result: The results of this study were 65 respondents (45.5%) aged 56-65 years with female sex totaling 109 respondents (76.2%) and in general 68 respondents (47.6%) had diabetes mellitus for more than 5 years and concluded: it was concluded that the majority of respondents experienced complications of cardiovascular system disorders as many as 56 respondents (39.2%)